Clinic Pathological Evaluation of Benign Breasts Lesion - Dr. Bharat Muljibhai Chaudhari; Dr. Ashish N Madiya (Tropical Journal of Pathology and Microbiology, 2021)
Introduction: Benign breast lesions are more common than malignant tumours. Hence recognizing them is important from the viewpoints of therapy and prognosis.Methodology: The materials for the study comprised of resected specimens of breast lesions received in the pathology department Karnataka Institute of Medical Sciences, Hubballi from May 2010 to April 2015.Results: A total of 600 cases of benign breast lesions were recorded. Fibroadenoma was the commonest benign breast lesions comprising 70.82%, followed by fibrocystic disease 12%, benign phyllodes tumour 8.3%. The majority of benign breast lesions occurred in the 2nd decade and 3rd decade. Conclusion: Benign breast lesions were common.Conclusion: The most frequently encountered breast lesions were fibroadenomas. So recognizing them is important for therapy and prognosis.